The Effect of Emergency Education for Health Cadres in Improving Early Detection of Catastrophic Diseases - Kasim, Felix (Jurnal FARMASIMED (JFM), 2024)
Catastrophic diseases, such as stroke, heart disease, and kidney failure, are the leading causes of morbidity and mortality in Indonesia. Early detection is crucial to prevent further complications. Health cadres play a strategic role in the early detection of these diseases; however, their understanding of emergency conditions remains limited. Therefore, emergency education is necessary to enhance the ability of health cadres in the early detection of catastrophic diseases.Objective: To analyze the impact of emergency education on improving the ability of health cadres in the early detection of catastrophic diseasesThis study employed a quasi-experimental design with a pre-test and post-test approach involving 50 health cadres in the working area of Puskesmas X. Data were collected through questionnaires before and after the emergency education intervention. Data analysis was conducted using univariate and bivariate statistical tests, with a paired t-test to examine differences before and after the intervention Univariate Analysis: Before the education was provided, 60% of health cadres had low knowledge levels, 30% were at a moderate level, and only 10% had a high level of knowledge. After the intervention, there was a significant increase, with 70% of cadres having a high level of knowledge and 30% in the moderate category.Bivariate Analysis: The paired t-test results showed a significant difference (p < 0.05) in the knowledge level of health cadres before and after receiving emergency education. Emergency education significantly improves the ability of health cadres in the early detection of catastrophic diseases. Therefore, this educational program should be continuously implemented to enhance the capacity of health cadres in efforts to prevent and detect catastrophic diseases in the community